Contextual Learning Strategies in Improving Students Understanding of Islamic Values - Amril Huda M; Andra Andra; Krim Ulwi (Journal of Social Science Utilizing Technology, 2025)
Background. Contextual Teaching and Learning strategies are an effective approach to improve students" understanding of Islamic values by relating the subject matter to real situations that are relevant to daily life. Purpose. This study aims to analyze the influence of contextual learning strategies in strengthening students" understanding of Islamic teachings. Method. The method used is a qualitative-based literature study with data tracing from scientific journals, books, and recent research reports. Results. The results of the analysis show that contextual learning is able to increase students" active engagement, strengthen their understanding of Islamic values, and motivate the application of these teachings in real life. In addition, the role of teachers as creative and innovative facilitators is the key to the successful implementation of this strategy. The implications of this study confirm the importance of integrating Islamic values and experiential learning strategies to create a meaningful and holistic educational process. Conclusion. Contextual learning strategies are effective in instilling Islamic values in an applicative and meaningful manner. This approach encourages student engagement and 21st century skill development. Its success requires the support of teachers, schools, and synergistic policies.